Associations of tumor necrosis factor alpha genetic variants with metabolic syndrome and type 2 diabetes mellitus in a Thai population - Metha Yaikwawong; Khanittha Kamdee; Kasarnchon Mek-yong; Somlak Chuengsamarn (PLoS ONE, 2026)
This work aimed to clarify how polymorphisms in the TNF gene relate to metabolic syndrome (MetS), type 2 diabetes mellitus (T2DM), and a broad spectrum of cardiometabolic characteristics, while also determining their impact on circulating TNF‑α concentrations. A total of 765 participants were genotyped for rs1800629 and rs361525, and serum TNF-α was also measured. To assess these relationships, multivariable logistic regression models—incorporating age, sex, and body mass index (BMI)—were applied to estimate adjusted odds ratios (aORs) and their corresponding 95% confidence intervals (CIs). Both variants were significantly associated with MetS: rs1800629 (crude OR = 2.22, 95% CI: 1.45–3.44, P < 0.001; adjusted OR = 3.13, 95% CI: 1.78–5.06, P < 0.001) and rs361525 (crude OR = 2.08, 95% CI: 1.07–4.21, P = 0.035; adjusted OR = 2.84, 95% CI: 1.17–7.31, P = 0.025). The rs1800629 variant was also linked to T2DM risk (adjusted OR = 2.61, 95% CI: 1.35–5.24, P = 0.006), whereas rs361525 showed no such association. Carriers of rs1800629 had higher mean TNF-α levels ( P < 0.05), with A allele carriers among T2DM patients showing the greatest elevation. Our findings indicate that the rs1800629 and rs361525 variants may contribute meaningfully to MetS susceptibility, and that rs1800629, in particular, shows a notable association with T2DM risk, underscoring its potential relevance in personalized metabolic risk assessment.